ANALISIS PENDAPATAN USAHATANI UBI KAYU (Manihot esculenta crantz) (Studi Kasus Desa Mojo Kecamatan Cluwak Kabupaten Pati) - Rofiatul Muizah; Suprapti Supardi; Shofia Nur Awami (MEDIAGRO, 2013)
This research aims to determine the production cost, revenue and income  of cassava farm, as well as the factors that influence cassava farm income in Mojo Village, Cluwak District, Pati Regency. Cassava farm income is obtained from the difference between total revenue (TR) and total cost (TC), the average number of explicit cost is Rp.7,824,782 per growing season, and the average number of cassava farm receipts is Rp.16,858,800 per growing season. Based on the calculation, it is known that average income of cassava farm is Rp.9,034,018, per growing season. According to data analysis using multiple linear regression, it is known that the coefficient of determination (R2) 0.918 stated that the ability of the model established by the independent variables in explaining the variability of the dependent variable is 91.8 percent, while the remaining 8.2 percent is explained by other variables. F test showed the value of F calculated probability value of 79.492 with asignificance of 0.000. T test showed variable cost of fertilizer, the amount of production, selling price and ownership has a significant probability value of 0.000, the variable of labor costs (outside the family) has a significance value of 0.085. Experience variable and pesticides cost have no influence effect on cassava farming income. Keywords: Cassava, income analysis, multiple linear regressions.